AN OVERVIEW 0F WRITING TEACHING APPROACHES - ajes, editor; Felix, Tans (Postgraduate School, Universitas Nusa Cendana, 2023)
In this essay, five major writing teaching approaches are described. The first is the controlled-composition approach. In this approach, writing is taught to improve students’ non-writing skills, that is, speaking, listening, reading, and other language aspects such as vocabulary and grammar. The second is the current-traditional rhetoric approach. In this approach, the aim is to improve students' writing by focusing on language components that are important to becoming a writer, including vocabulary, sentence structures, paragraph structures, and essay development. The third approach is the process approach, which views writing as an individual process. In that sense, the intervention of writing teachers in the teaching of writing should be minimal, if not absent altogether, unless student writers want their teachers' help in writing. The fourth approach is the genre approach. In this approach, writing is seen as a social phenomenon in which certain models of writing must be well-mastered by student writers so that they can later produce them within their society. The last is a contextual approach which combines both process and genre approaches. In this approach, the teaching and learning of writing are based on the writing teachers' analysis of their students' potentials, interests, and needs in writing. It is suggested that the contextual approach be applied in our schools because it is more relevant along our students' journey to becoming great writers.